Immunoengineering in glioblastoma imaging and therapy. (12th August 2019) - Zanganeh, Steven; Georgala, Petrina; Corbo, Claudia; Arabi, Leila; Ho, Jim Q.; Javdani, Najme; Sepand, Mohammad R.; Cruickshank, Kiara; Campesato, Luis F.; Weng, Chien‐Huan; Hemayat, Saeed; Andreou, Chrysafis; et al.
Abstract: Patients diagnosed with glioblastoma have poor prognosis. Conventional treatment strategies such as surgery, chemotherapy, and radiation therapy demonstrated limited clinical success and have considerable side effects on healthy tissues. A central challenge in treating brain tumors is the poor permeability of the blood–brain barrier (BBB) to therapeutics. Recently, various methods based on immunotherapy and nanotechnology have demonstrated potential in addressing these obstacles by enabling precise targeting of brain tumors to minimize adverse effects, while increasing targeted drug delivery across the BBB. In addition to treating the tumors, these approaches may be used in conjunction with imaging modalities, such as magnetic resonance imaging and positron emission tomography to enhance the prognosis procedures. This review aims to provide mechanistic understanding of immune system regulation in the central nervous system and the benefits of nanoparticles in the prognosis of brain tumors. This article is characterized under: Diagnostic Tools > in vivo Nanodiagnostics and Imaging Nanotechnology Approaches to Biology > Cells at the Nanoscale Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Importance of the immune system in tumor promotion/rejection.